PEANUT SHELLING MACHINE USING A PETROL ENGINE - William Laia; Nani Sri Rezeki (Journal of Golden Generation Engineering, 2025)
This study discusses a peanut shelling machine driven by a gasoline-engineered motor . In Indonesia, many processed peanut products require peanuts as a component, such as salted peanuts, peanut oil, peanut paste, peanut tofu, and others. Manual peanut shelling is usually inefficient and time-consuming. Therefore, with this machine, which can automatically peel peanuts, it will greatly help save time and increase production capacity. Based on planning calculations for the planned components, the following data was obtained: Gasoline engine used = 5.5 Hp , Pad = 6005 , Belt length to peeler = 65 inches , Belt length to blower = 25 inches , Diameter pulley blower = 4 inches , Pulley diameter peeler = 11 inches , Diameter pulley driver = 2 inches . After analyzing the production/manufacturing costs of this machine, the price for manufacturing 1 peanut peeling machine was Rp4,019,372.24 .